2020
DOI: 10.35434/rcmhnaaa.2020.131.627
|View full text |Cite
|
Sign up to set email alerts
|

Metodologías cuantitativas: Cálculo del tamaño de muestra con STATA y R

Abstract: El cálculo de tamaño de muestra es un aspecto esencial del diseño de estudios cuantitativos. Un adecuado tamaño de muestra nos permite determinar cuál es la mínima cantidad de participantes necesarios para probar nuestra hipótesis de interés. De esta manera, podemos reducir costos, maximizar el uso de nuestros recursos de investigación y garantizar la factibilidad del estudio. Contradictoriamente, a pesar de su relevancia muy pocos investigadores dominan esta habilidad. Esta revisión tiene por objeto revisar l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Prior to conducting this research, the sample size was calculated in order to ensure robust results (Quispe et al, 2020). After jointly estimating the u (in reference to the number of variables) and f 2 (effect size in linear regression models) statistics, it was obtained that the minimum sample had to be a total of 98 subjects to be able to carry out the linear regression technique, something that is fulfilled since we have a total sample of 118 students.…”
Section: Methods Type Of Study and Participantsmentioning
confidence: 99%
“…Prior to conducting this research, the sample size was calculated in order to ensure robust results (Quispe et al, 2020). After jointly estimating the u (in reference to the number of variables) and f 2 (effect size in linear regression models) statistics, it was obtained that the minimum sample had to be a total of 98 subjects to be able to carry out the linear regression technique, something that is fulfilled since we have a total sample of 118 students.…”
Section: Methods Type Of Study and Participantsmentioning
confidence: 99%
“…In this context, the study population consisted of 1,343 undergraduate students from the Faculty of Life Sciences of the UEA, including the careers of Environmental Engineering, Tourism and Biology. According to Quispe et al (2020), the sample is the number of representative elements of a target population that are required. This number is determined by a calculation procedure that allows the study hypothesis to be confirmed or rejected depending on the appropriate sample size.…”
Section: Methodsmentioning
confidence: 99%
“…Según el número de participantes, la RSL arrojó que los estudios utilizaron con mayor frecuencia una muestra dentro del rango 1 a 100 participantes (50 %). El cálculo del tamaño muestral es un aspecto esencial en estudios cuantitativos para la generalización de resultados (Quispe et al, 2020). Ninguno de los estudios analizados determinó la mínima cantidad de participantes para la comprobación de sus hipótesis.…”
Section: Características Generalesunclassified